Program Kebun Pekarangan Rumah - Mildayanti Mildayanti; Dwiyanti Dwiyanti; Asriyani Amrullah; Siti Nardiyah Muhrami; Muh. Irshan Sachir (Yayasan Literasi Sains Indonesia, 2025)
The Home Garden Program in Dusun Bancee, Poleonro Village, Libureng Subdistrict, represents a community-based intervention aimed at improving local food security, promoting sustainable land use, and strengthening household economic resilience. This initiative encourages the productive use of residential yard space by cultivating vegetables, fruits, medicinal plants (TOGA), and spices. The program adopts a participatory and educational approach, involving regular training, technical workshops, and field assistance. Initial outcomes indicate significant improvements in residents' gardening skills, better dietary patterns through access to fresh produce, and reduced household food expenses. Moreover, it fosters social values such as mutual cooperation and independence through collective gardening efforts. Environmentally, the program enhances awareness of organic farming practices and supports local biodiversity conservation. Beyond improving quality of life, it serves as an innovative and replicable model of sustainable home garden management for other rural communities. The program’s success highlights how agroecology-based local approaches can provide practical, impactful solutions to food, economic, and environmental challenges at the village level.